The Moderator Role of Managerial Overconfidence in the Relationship between R&D Volatility and Firm Value: An Application in Borsa Istanbul - Nur, Tuğba; Ege, Ilhan; Topaloglu, Emre Esat (My University, 2023)
Purpose: The study aims to reveal the moderating role of managerial overconfidence in the link between R&D volatility and firm value in firms operating in the Metal Goods Sector of Borsa Istanbul during the period 2010-2020. Design/Methodology: The moderating role of managerial overconfidence in the linkage between R&D volatility and firm value is investigated with panel data analysis. Findings: The short-run estimates reveal positive linkage determined between R&D volatility and firm value. We also reveal that managerial overconfidence positively moderates the link between R&D volatility and firm value. In this direction, the effect of R&D volatility on firm value is higher and positive in firms where managers have excessive self-confidence. Limitations: The fact that the sample consists of students who are only in Gaziantep and the use of three variables as a brand component are the limitations of the study. Originality/Value: The number of studies in the literature on the relevant period and sample is limited. Therefore, the study contributes to the literature and is original.
Keywords: BIST; Firm Value; R&D Volatility; Managerial Overconfidence